The Impact of Light Wavelength and Darkness on Metabolite Profiling of Korean Ginseng: Evaluating Its Anti-Cancer Potential against MCF-7 and BV-2 Cell Lines - Sadiq, Nooruddin Bin; Kwon, Hyukjoon; Park, Nam Il; Hamayun, Muhammad; Jung, Je-Hyeong; Yang, Seung-Hoon; Jang, Soo-Won; Kabadayi, Seda Nur; Kim, Ho-Youn; Kim, Young-Joo (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Korean ginseng is a source of functional foods and medicines; however, its productivity is hindered by abiotic stress factors, such as light. This study investigated the impacts of darkness and different light wavelengths on the metabolomics and anti-cancer activity of ginseng extracts. Hydroponically-grown Korean ginseng was shifted to a light-emitting diodes (LEDs) chamber for blue-LED and darkness treatments, while white fluorescent (FL) light treatment was the control. MCF-7 breast cancer and lipopolysaccharide (LPS)-induced BV-2 microglial cells were used to determine chemo-preventive and neuroprotective potential. Overall, 53 significant primary metabolites were detected in the treated samples. The levels of ginsenosides Rb1, Rb2, Rc, Rd, and Re, as well as organic and amino acids, were significantly higher in the dark treatment, followed by blue-LED treatment and the FL control. The dark-treated ginseng extract significantly induced apoptotic signaling in MCF-7 cells and dose-dependently inhibited the NF-?B and MAP kinase pathways in LPS-induced BV-2 cells. Short-term dark treatment increased the content of Rd, Rc, Rb1, Rb2, and Re ginsenosides in ginseng extracts, which promoted apoptosis of MCF-7 cells and inhibition of the MAP kinase pathway in BV-2 microglial cells. These results indicate that the dark treatment might be effective in improving the pharmacological potential of ginseng.